Effects of multidisciplinary pain treatment can be predicted without elaborate questionnaires - Fischer, Christian; Neubauer, Eva; Adams, Hanne S.; Schiltenwolf, Marcus; Wang, Haili (International orthopaedics, 2014)
Low back pain is one of the most common and expensive diseases of Western societies. Psychosocial factors such as low social status, depression, or work dissatisfaction are known to promote chronicity of low back pain. With a multidisciplinary approach, better outcomes can be achieved than with purely biomedical treatment. Optimal patient selection for multidisciplinary therapy reduces costs and labour. This study investigated whether elaborated questionnaires exceed simple items in predicting multimodal therapy success.